Integrasi Kecerdasan Intelektual ( IQ), Kecerdasan Emosi (EQ) dan Kecerdasan Spiritual (SQ) dalam Meningkatkan Etos Kerja - Noer Rohmah (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2018)
Intelligence is a characteristic of human excellence in understanding, decided, anticipate and face things. Several studies indicated that IQ only plays 5%-20% in contributing someone succeed. According to the Carnegie Institute of Technology, USA, from 10.000 successful people, 15% caused by intellectual ability, 85% due to personality. Many people are smart academically, but failed to work and social life. They deliver a split personality (there is no integration between mind and soul). These conditions can raise the concerned multi-dimensional crisis. These phenomena has been realized by the experts that success is defined not merely by the power of the mind and intellect, simply more influenced by emotional intelligence (EQ) and spiritual intelligence (SQ). Therefore, education should be implemented in a balanced way, with the same attention and emphasis in IQ, EQ and SQ. This is where the importance of integration between IQ, EQ and SQ, in improving the work ethic for a more meaningful life.